2006
DOI: 10.1029/2006gc001278
|View full text |Cite
|
Sign up to set email alerts
|

A GEOCLIM simulation of climatic and biogeochemical consequences of Pangea breakup

Abstract: [1] Large fluctuations in continental configuration occur throughout the Mesozoic. While it has long been recognized that paleogeography may potentially influence atmospheric CO 2 via the continental silicate weathering feedback, no numerical simulations have been done, because of the lack of a spatially resolved climate-carbon model. GEOCLIM, a coupled numerical model of the climate and global biogeochemical cycles, is used to investigate the consequences of the Pangea breakup. The climate module of the GEOCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 66 publications
(97 reference statements)
6
139
1
Order By: Relevance
“…This is a useful first-order approach but cannot capture spatially explicit effects or the effect of changing continental configurations on temperature and runoff [18][19][20][21], nor the location of highly reactive volcanic rocks with respect to regional or local climate and vegetation. Therefore, we now extend the modelling approach of Taylor et al [10] into two dimensions (latitude by longitude) to investigate the effects of regional and seasonal variations in the activity of vegetation and mycorrhizal fungi as well as climate on continental weathering processes over geological time.…”
Section: Introductionmentioning
confidence: 99%
“…This is a useful first-order approach but cannot capture spatially explicit effects or the effect of changing continental configurations on temperature and runoff [18][19][20][21], nor the location of highly reactive volcanic rocks with respect to regional or local climate and vegetation. Therefore, we now extend the modelling approach of Taylor et al [10] into two dimensions (latitude by longitude) to investigate the effects of regional and seasonal variations in the activity of vegetation and mycorrhizal fungi as well as climate on continental weathering processes over geological time.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, available records suggest its strong shoaling at that time (Pälike et al 2012;Slotnick et al, 2014), which according to Komar et al (2013) hardly conforms to the intense weathering deduced form carbon cycle models. However, previous GEOCLIM modeling showed that a constant silicate weathering flux does not mean a fixed pCO 2 (and thus a fixed CCD), due to the major role played by continental configuration on pCO 2 values (Donnadieu et al, 2006). The second observation is based on δ 7 Li chemistry of Paleocene and Eocene marine sediments, compiled by Misra and Froelich (2012).…”
Section: Are Modeled Silicate Weathering Fluxes Overestimated For Thementioning
confidence: 99%
“…The model uses an ocean geometry divided into two polar oceans (including a photic zone and a deep ocean reservoir), a low-to mid-latitude ocean (including a photic zone, a thermocline and a deep ocean reservoir), two epicontinental seas (both with a photic zone and a deep epicontinental reservoir) and the atmosphere. A full description of GEOCLIM and its components COMBINE and FOAM can be found in Goddéris and Joachimski (2004) and Donnadieu et al (2006).…”
Section: Modeling the Impact Of Neothetys Closurementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the Mesozoic amalgamation and subsequent dismemberment of the Pangean supercontinent has played a vital role in the paleogeographic, paleobiological, tectonic and climatic evolution of the planet as it resulted in the opening and closure of oceanic gateways that regulated and impacted climate patterns and the paleogeography of the planet (Cocks and Torsvik, 2002;Scotese et al, 1999;Torsvik and Van der Voo, 2002;Golonka et al, 2006;Seton et al, 2012). Creating interactive digital models of paleogeography enables the estimation of land and ocean distributions that can be linked to paleoclimate simulations as demonstrated by Gyllenhaal et al (1991), Ross et al (1992), Donnadieu et al (2006) and others. A variety of global and regional paleogeographic models have been constructed, but their differences and uncertainties are difficult to assess.…”
Section: Introductionmentioning
confidence: 99%